Enhancing Sportirena testing through custom Selenium Automation tools for PT Technova - naufal azzam, julian; atmadiputra, pradana; normalisa (Liaison Journal of Engineering, 2024)
This research paper, entitled "Improving the Testing of Sportirena through Personalized Selenium Automation Tools," highlights the urgent requirement for automated testing within the Sportirena platform. In a similar manner to enhancing fire resistance in composite sandwich panels, which aims to strengthen against potential dangers, our investigation concentrates on enhancing the reliability of Sportirena's application. We have developed customized automation tools, comparable to the addition of fire retardants, utilizing Selenium, with a specific focus on user authentication. The results demonstrate significant improvements in testing efficiency, coverage, and defect detection when compared to manual techniques. The insights obtained from existing literature support our findings and validate the chosen methodology. By drawing parallels between fire resistance in composite panels and automated testing in Sportirena, this study contributes to the overall objective of ensuring safety and resilience in intricate systems. Keywords: testing, efficiency, coverage, and defect detection.